Antihypertensive and Immunomodulatory Effects of Defatted Corn Germ Hydrolysates: An in vivo Study - Zhu, Jiaqi; Li, Jing; Guo, Yiting; Quaisie, Janet; Hong, Chen; Ma, Haile (Frontiers in Nutrition, 2021)
This study investigated the antihypertensive and immunomodulatory effects of defatted corn germ hydrolysates (DCGHs) in vivo and their potential regulatory mechanisms. The systolic blood pressure (SBP) of spontaneously hypertensive rats (SHRs) was significantly reduced (10.30%) by the long-term intragastric administration of DCGHs (high doses). Also, there was drastic inhibition of angiotensin-I-converting enzyme (ACE) activity in the lung, kidney, and heart tissues by 24.53%, 22.28%, and 12.93%, respectively. It could regulate the blood pressure by adjusting the balance between endothelium-derived vasoconstrictor factors and endothelium-derived relaxing factors. Meanwhile, DCGHs enhanced the phagocytosis of mononuclear macrophages, cellular immunity, and humoral immunity of ICR mice by increasing the phagocytic index of mononuclear macrophages (23.71%), ear swelling degree (44.82%), and antibody levels (52.32%). Moreover, it stimulated the release of immunoactive substances (e.g., lysozyme, interferon-γ, immunoglobulin G, and complement 3). Consequently, DCGHs could suitably be used in the formulation of novel functional foods with antihypertensive and immunomodulatory properties.